Evaluation of fly ash and polypropylene in production of composite materials - Yildiz, Tulay; Argunhan, Zeki; Haksever, Aysen (My University, 2012)
More than 10 million tons of fly ash produced in power plants and polypropylene wastes cause environmental pollution in Turkey. Not only the environmental problems they create, but also the fact that demand for raw material sources increases rapidly make fly ashes and waste polypropylene necessary to be researched. In this study the usability of the fly ashes and polypropylene wastes of Soma and Afsin-Elbistan Power Plants in producing new composite materials has been investigated. Materials which possess new properties such as composite type isolation have been formed by melting down the polypropylene wastes that are used as combining elements and by mixing this with fly ash in different percentages. The thermal conductivity, endurance against pressure pull-corrosion, and the rates of water absorption of these materials were analyzed experimentally and both stated and interpreted in the graphics. By this way, these two materials can be recovered by both lessening the environmental problems and providing income for economy by means of saving energy. © Sila Science.
Keywords: Composite materials; Fly ash; Polypropylene